Absolutely normal chaos - Creech, Sharon (New York, N.Y. : HarperCollinsPublishers, 1997)
Thirteen-year-old Mary Lou grows up considerably during the summer while learning about romance, homesickness, death, and her cousin's search for his biological father
900
Keywords: Homesickness -- Fiction; Death -- Fiction; Cousins -- Fiction; Fathers and sons -- Fiction